Density and potential fluctuations in the edge plasma of the Uragan-3m torsatron - Sorokovoy, E.L.; Chechkin, V.V.; Grigor’eva, L.I.; Chechkin, A.V.; Gonchar, V.Yu.; Volkov, E.D.; Nazarov, N.I.; Tsybenko, S.A.; Lozin, A.V.; Litvinov, A.P.; Kulaga, A.Ye.; Mironov, Yu.K.; et al. (Вопросы атомной науки и техники, 2002)
Ion saturation current and floating potential fluctuations are recorded by movable array of 4 Langmuir probes near the boundary of the confinement region in the l = 3/m = 9 Uragan-3M torsatron with an RF produced and heated plasma. On the basis of these data main spectral and time characteristics of the low frequency electrostatic turbulence have been derived. The existence of the radial electric field shear and reversal of poloidal phase velocity of the fluctuations at the plasma boundary have been confirmed. The time function of the turbulent E×B particle flux contains intermittent bursts with the amplitude multiply exceeding the average flux. Up to 70% of the total fluctuating flux is carried in these bursts.